2008
DOI: 10.2144/000112812
|View full text |Cite
|
Sign up to set email alerts
|

Detection of S-phase Cell Cycle Progression using 5-ethynyl-2′-deoxyuridine Incorporation with Click Chemistry, an Alternative to using 5-bromo-2′-deoxyuridine Antibodies

Abstract: The 5-bromo-2'-deoxyuridine (BrdU) labeling of cells followed by antibody staining has been the standard method for direct measurement of cells in the S-phase. Described is an improved method for the detection of S-phase cell cycle progression based upon the application of click chemistry, the copper(I)-catalyzed variant of the Huisgen [3+2] cycloaddition between a terminal alkyne and an azide. 5-ethynyl-2'-deoxyuridine (EdU) is a nucleoside analog of thymidine that is incorporated into DNA during active DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
207
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(215 citation statements)
references
References 13 publications
7
207
0
1
Order By: Relevance
“…EdU is one of the nucleoside analogs used for this purpose [13]. When EdU is added to the culture for a short enough period of time, it was possible to distinguish the CD4 + T cells that were synthesizing DNA ( Fig.…”
Section: Evaluation Of S Phase Using Edu (A Nucleoside Analog)mentioning
confidence: 99%
“…EdU is one of the nucleoside analogs used for this purpose [13]. When EdU is added to the culture for a short enough period of time, it was possible to distinguish the CD4 + T cells that were synthesizing DNA ( Fig.…”
Section: Evaluation Of S Phase Using Edu (A Nucleoside Analog)mentioning
confidence: 99%
“…Importantly, the same limitation in interpretation applies to other methods which rely on incorporation of an analog into DNA (e.g., tritiated thymidine or fluorogenic deoxyuridine). 65 A recent study of replication marker expression in human β-cells demonstrated that co-expression of two or more markers more accurately discriminates between quiescent and replicating β-cells. 66 Expression of Ki67 is used routinely as a proliferation marker in immunohistochemical studies.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…However, a potential alternative could be to use 5-ethynyl-2′-deoxyuridine (EdU), another thymidine analog that is, similar to BrdU, incorporated efficiently in replicating DNA 41 . Visualization of EdU using 'click chemistry" does not require acid hydrolysis 42 , and may therefore more suitable for some antibodies.…”
Section: Discussionmentioning
confidence: 99%